Screening for gestational diabetes mellitus based on different risk profiles and settings for improving maternal and infant health - Tieu, Joanna (Cochrane Database Syst Rev, 2017)
BACKGROUND: Gestational diabetes mellitus (GDM) is a form of diabetes that occurs in pregnancy. Although GDM usually resolves following birth, it is associated with significant morbidities for mothers and their infants in the short and long term. There is strong evidence to support treatment for GDM. However, there is uncertainty as to whether or not screening all pregnant women for GDM will improve maternal and infant health and if so, the most appropriate setting for screening. This review updates a Cochrane Review, first published in 2010, and subsequently updated in 2014. OBJECTIVES: To assess the effects of screening for gestational diabetes mellitus based on different risk profiles and settings on maternal and infant outcomes. SEARCH METHODS: We searched Cochrane Pregnancy and Childbirth's Trials Register (31 January 2017), ClinicalTrials.gov, the WHO International Clinical Trials Registry Platform (ICTRP) (14 June 2017), and reference lists of retrieved studies. SELECTION CRITERIA: We included randomised and quasi‐randomised trials evaluating the effects of different protocols, guidelines or programmes for screening for GDM based on different risk profiles and settings, compared with the absence of screening, or compared with other protocols, guidelines or programmes for screening. We planned to include trials published as abstracts only and cluster‐randomised trials, but we did not identify any. Cross‐over trials are not eligible for inclusion in this review. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed study eligibility, extracted data and assessed the risk of bias of the included trials. We resolved disagreements through discussion or through consulting a third reviewer. MAIN RESULTS: We included two trials that randomised 4523 women and their infants. Both trials were conducted in Ireland. One trial (which quasi‐randomised 3742 women, and analysed 3152 women) compared universal screening versus risk factor‐based screening, and one trial (which randomised 781 women, and analysed 690 women) compared primary care screening versus secondary care screening. We were not able to perform meta‐analyses due to the different interventions and comparisons assessed. Overall, there was moderate to high risk of bias due to one trial being quasi‐randomised, inadequate blinding, and incomplete outcome data in both trials. We used GRADEpro GDT software to assess the quality of the evidence for selected outcomes for the mother and her child. Evidence was downgraded for study design limitations and imprecision of effect estimates. Universal screening versus risk‐factor screening (one trial) Mother More women were diagnosed with GDM in the universal screening group than in the risk‐factor screening group (risk ratio (RR) 1.85, 95% confidence interval (CI) 1.12 to 3.04; participants = 3152; low‐quality evidence). There were no data reported under this comparison for other maternal outcomes including hypertensive disorders of pregnancy, caesarean birth, perineal trauma, gestational weight gain, postnatal depression, and type 2 diabetes. Child Neonatal outcomes: large‐for‐gestational age, perinatal mortality, mortality or morbidity composite, hypoglycaemia; and childhood/adulthood outcomes: adiposity, type 2 diabetes, and neurosensory disability, were not reported under this comparison. Primary care screening versus secondary care screening (one trial) Mother There was no clear difference between the primary care and secondary care screening groups for GDM (RR 0.91, 95% CI 0.50 to 1.66; participants = 690; low‐quality evidence), hypertension (RR 1.41, 95% CI 0.77 to 2.59; participants = 690; low‐quality evidence), pre‐eclampsia (RR 0.80, 95% CI 0.36 to 1.78; participants = 690;low‐quality evidence), or caesarean section birth (RR 1.00, 95% CI 0.80 to 1.27; participants = 690; low‐quality evidence). There were no data reported for perineal trauma, gestational weight gain, postnatal depression, or type 2 diabetes. Child There was no clear difference between the primary care and secondary care screening groups for large‐for‐gestational age (RR 1.37, 95% CI 0.96 to 1.96; participants = 690; low‐quality evidence), neonatal complications: composite outcome, including: hypoglycaemia, respiratory distress, need for phototherapy, birth trauma, shoulder dystocia, five minute Apgar less than seven at one or five minutes, prematurity (RR 0.99, 95% CI 0.57 to 1.71; participants = 690; low‐quality evidence), or neonatal hypoglycaemia (RR 1.10, 95% CI 0.28 to 4.38; participants = 690; very low‐quality evidence). There was one perinatal death in the primary care screening group and two in the secondary care screening group (RR 1.10, 95% CI 0.10 to 12.12; participants = 690; very low‐quality evidence). There were no data for neurosensory disability, or childhood/adulthood adiposity or type 2 diabetes. AUTHORS' CONCLUSIONS: There are insufficient randomised controlled trial data evaluating the effects of screening for GDM based on different risk profiles and settings on maternal and infant outcomes. Low‐quality evidence suggests universal screening compared with risk factor‐based screening leads to more women being diagnosed with GDM. Low to very low‐quality evidence suggests no clear differences between primary care and secondary care screening, for outcomes: GDM, hypertension, pre‐eclampsia, caesarean birth, large‐for‐gestational age, neonatal complications composite, and hypoglycaemia. Further, high‐quality randomised controlled trials are needed to assess the value of screening for GDM, which may compare different protocols, guidelines or programmes for screening (based on different risk profiles and settings), with the absence of screening, or with other protocols, guidelines or programmes. There is a need for future trials to be sufficiently powered to detect important differences in short‐ and long‐term maternal and infant outcomes, such as those important outcomes pre‐specified in this review. As only a proportion of women will be diagnosed with GDM in these trials, large sample sizes may be required.